Racial Disparities in Outcomes of Women Undergoing Myomectomy. Issue 6 (December 2021) - Dallas, Kai; Dubinskaya, Alexandra; Andebrhan, Sarah B.; Anger, Jennifer; Rogo-Gupta, Lisa J.; Elliott, Christopher S.; Ackerman, A. Lenore
Abstract : OBJECTIVE: To assess the association of racial and socioeconomic factors with outcomes of abdominal myomectomies. METHODS: All women undergoing abdominal myomectomy in California from 2005 to 2012 were identified from the OSHPD (Office of Statewide Health Planning and Development) using appropriate International Classification of Diseases and Current Procedural Terminology codes. Demographics, comorbidities, surgical approaches, and complications occurring within 30 days of the procedure were identified. Multivariate associations were assessed with mixed effects logistic regression models. RESULTS: The cohort of 35, 151 women was racially and ethnically diverse (White, 38.8%; Black, 19.9%; Hispanic, 20.3%; and Asian, 15.3%). Among all procedures, 33, 906 were performed through an open abdominal approach, and 1, 245 were performed using a minimally invasive approach. Proportionally, Black patients were more likely than White patients to have open procedures, and open approaches were associated with higher complication rates. Overall, 2, 622 (7.5%) women suffered at least one complication. Although severe complications did not vary by race or ethnicity, Black (9.0%), Hispanic (7.9%), and Asian (7.5%) patients were more likely to suffer complications of any severity compared with White patients (6.7%, P <.001). As compared with patients with private insurance (6.4%), those with indigent payer status (Medicaid [12.1%] and self-pay [11.1%]) had higher complication rates ( P <.001). Controlling for all factors, Black and Asian patients were more likely to suffer complications compared with White patients. CONCLUSION: The overall complication rate after abdominal myomectomy was 7.5%. Comorbidities, an open approach, and indigent payer status were associated with increased complication risk. Controlling for all factors, Black and Asian patients still had increased risks of complications. Abstract : Ethnicity was associated with the risk of complications after myomectomy.